Estimation of Acacia melanoxylon unbleached Kraft pulp brightness by NIR spectroscopy - Santos, A.J.A. (2017)
Submitted by Maria Silva (mfsilva@ipcb.pt) on 2017-05-31T10:46:30Z No. of bitstreams: 1 2015_Estimation of Acacia melanoxylon unbleached Kraft pulp brightness by NIR spectroscopy-2015.pdf: 171445 bytes, checksum: edb4d2f88d3248a2db702286af330fbb (MD5)